Immunotoxicological impact of engineered nanomaterial exposure: mechanisms of immune cell modulation - Wang, Xiaojia (2013)
Engineered nanomaterials (ENM) are increasingly being utilized in many consumer products and various medical applications thereby leading to the potentiality of increased human exposures. Assessment of the adverse effects on the immune system is an important component for evaluating the overall health and safety of ENM. Tasked with eliminating pathogens and removing cancerous cells, the immune system is constantly functioning to maintain homeostasis. Small modifications to the immune system which may occur following ENM exposure, could lead to impaired protection or an inappropriate immune response resulting in autoimmunity and damage to the host. This review seeks to survey and evaluate the current literature to better understand the impact of ENM exposure on cells critical to the innate and adaptive immune systems.